Aleph i wiersze odrzucone. "Odpowiedzi literackie" na łamach "Nadodrza" w latach 1976-1978 = Aleph and rejected poems. "Literary answers " in "Nadodrze" in the years 1976-1978 - Szott, Mirosława (1987- ) (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Andrzej Krzysztof Waśkiewicz ran "Literary Answers" in the magazine "Nadodrze" between 1976-1978. He used the pseudonym "Aleph" taken from the novel by Jorge Luis Borges. The figure created by a young editor at that time (at the age of 35) was associated, in his early years, with a little-known futurist group called "Katarynka Warszawska", gathered around Kazimierz Brzeski. Alepha's job was to evaluate the poetry of newcomers, to answer their questions, and to enable the publication of some poems. The master had many opportunities to remember his supposedly youthful days, special publications, as well as to get involved in polemics and jokes with his fellows (e.g. J. Koniusz). In October 1978, we lost track of Alephie (in 1979 Waśkiewicz left Zielona Góra and moved to Gdańsk). His farewell note, which he wrote, did not appear in "Nadodrze" because the editor-in-chief, Tadeusz Kajan, rejected the text. Waśkiewicz admitted to this game, only after 17 years, in "Komunikaty", which was edited by Eugeniusz Kurzawa. The purpose of this article is to examine and describe this well-implemented mystification.
Keywords: list; Nadodrze (czasopismo); wiersze; życie literackie; Aleph (pseud.); Kajan, Tadeusz; Kurzawa, Eugeniusz (poeta; 1954- ); Waśkiewicz, Andrzej Krzysztof (1941-2012); letter; poems; literary life